Experimental Study on the Boiling Heat Transfer Characteristics in Micro-channel with Two Different Working Medium - Chen Yumin; Liu Dongyao (Zhileng xuebao, 2016)
Experiments are performed in rectangular micro-channels (dH =0.293 mm) under the condition of different mass flux and heat flux to evaluate the flow boiling heat transfer characteristics with deionized water and anhydrous ethanol. Research in micro-channels is aimed at studying the influence rule of state parameters of fluid properties, flow and heat transfer process of boiling heat transfer characteristics. According to the calculation and comparison of experimental data, the relationship between boiling heat transfer coefficient and thermal physical properties of fluid, mass flux, heat flux, vapor qualities, Boiling number are presented respectively. The results show that boiling heat transfer coefficient decreases with the increasing of heat flux, vapor qualities and Boiling number. Nucleate boiling is dominant in the process of heat transfer. Under the same condition the boiling heat transfer coefficient of deionized water is obviously higher than the boiling heat transfer coefficient of anhydrous ethanol. The heat transfer coefficient of deionized water increases with the increasing of mass flux, but anhydrous ethanol has no significant changes with mass flux. The results from heat transfer correlation taking scale effect and fluid properties into consideration have 14.2% and 16.6% MAE (Mean Absolute Error) for deionized water and anhydrous ethanol respectively. It proves that the heat transfer correlation has good applicability of predicting the boiling heat transfer coefficient in micro-channels.